Biochemical and structural studies of target lectin SapL1 from the emerging opportunistic microfungus Scedosporium apiospermum - Dania Martínez-Alarcón (Nature Portfolio, 2021)
Abstract Scedosporium apiospermum is an emerging opportunistic fungal pathogen responsible for life-threatening infections in humans. Host–pathogen interactions often implicate lectins that have become therapeutic targets for the development of carbohydrate mimics for antiadhesive therapy. Here, we present the first report on the identification and characterization of a lectin from S. apiospermum named SapL1. SapL1 was found using bioinformatics as a homolog to the conidial surface lectin FleA from Aspergillus fumigatus known to play a role in the adhesion to host glycoconjugates present in human lung epithelium. In our strategy to obtain recombinant SapL1, we discovered the importance of osmolytes to achieve its expression in soluble form in bacteria. Analysis of glycan arrays indicates specificity for fucosylated oligosaccharides as expected. Submicromolar affinity was measured for fucose using isothermal titration calorimetry. We solved SapL1 crystal structure in complex with α-methyl-L-fucoside and analyzed its structural basis for fucose binding. We finally demonstrated that SapL1 binds to bronchial epithelial cells in a fucose-dependent manner. The information gathered here will contribute to the design and development of glycodrugs targeting SapL1.